(untitled) (diségno, 2020)
The 18th International Congress of Graphic Design in Architecture was held on September 24 and 25, 2020. This event is organized every other year by the teachers of Graphic Design of the Higher Technical Schools of Architecture in Spain. This year, the Scientific Committee designated Zaragoza as the organizational seat, on the general theme of The graphic heritage. The graphics of heritage (read more).